Empirical Analysis of the Speculative Efficiency Hypothesis - LU, XIANGYU (2012)
Exchange market is one of the most important financial markets. An accurate prediction for future spot exchange rate is curial for modern businesses, specially the multinational enterprises, to hedge the volatility of currency exchange rate. The exchange rate also influence countries’ import and export significantly. If the home currency appreciates, this fact will significantly increase the amount of import and reduce the amount of export. In the opposite, any depreciation will help boosting the export and inhibit the import behaviour. Consequently, a mechanism of efficient forward exchange rate estimation is necessary based on both macro and micro-economic perspectives.